Transformation of Teaching Practices in the Digital Era: A Sociological Perspective on Changes in Social Interaction and the Reproduction of Inequality - Muh. Ahyar; Sarwadi Sarwadi; Wirham Wirham; Nursamak; Sahril Sidik; M. Fathul Aziz; Umar Perwira; Ahmad Yani (Academicus: Journal of Teaching and Learning, 2026)
This study examines changes in teaching practices in the digital era from the perspective of Sociology of Education, with a focus on social interaction and educational inequality. The study employed a mixed-methods design by integrating quantitative and qualitative data collected from higher education students and lecturers in Nusa Tenggara Barat, Indonesia. The quantitative phase measured several indicators, including patterns of teacher–student interaction, digital participation, access to technology, digital literacy, and perceptions of learning inequality through questionnaire-based surveys. The qualitative phase involved interviews and classroom observations to explore participants’ experiences and interpretations of digital learning practices. The quantitative findings indicate that the use of digital learning platforms is associated with changes in interaction patterns, particularly in the shift from direct classroom communication toward technology-mediated learning environments. Survey results also suggest differences in digital access, participation, and learning engagement among students from different socio-economic backgrounds. These findings were further supported by qualitative data showing that lecturers and students experienced changes in classroom authority, communication patterns, and assessment practices due to the increasing use of digital platforms and data-based evaluation systems. The integrated findings suggest that digital learning environments provide greater flexibility and opportunities for independent learning; however, these benefits may not be equally experienced by all students. Variations in technological access and digital literacy appear to influence the quality of participation and engagement in online learning. In addition, the study found indications that digital participation is increasingly shaped by measurable online activities and platform-based monitoring systems. Overall, the study highlights that the digitalization of teaching practices may reshape existing educational interactions and inequalities, emphasizing the importance of inclusive and critical approaches in digital pedagogy.